Pengendalian Internal Pembelian Kredit dan Hutang Terhadap Pengeluaran Kas Pada PT Neo Kosmetika Industri - Tony Renhard Sinambela; Lidia Baktisa Napitupulu (Mulia Pratama, 2023)
This study aimsto analyze theinternal controls occurs with the companyandformulateproposalsnecessary repairs. The research methodology uses observation, interviewsand put thequestionnaires to theemployees ofthe company. The results showsthat theinternal controlhasseveraladvantagesanddisadvantages.The good implementation of internal controlinthiscompanyisrecording procedureshave beenimplemented, the formgivenin sequenceandnumberingprintedandauthorizedbythe respectiveheads of thesection. On the other hand, the weaknessthat should receivethe attention ofmanagementis some section still have double job responsibility. Based onthe analysis of research, it can be concludedthatinternal control over purchasing, accounts payableand cash payment has not beeneffective. The authorsuggested thatthe companymaking purchase order based on request from warehouse, the company must make an account payable subsidiary and making a special section called cashier section.